Influence of Metal ions, Surfactants and Organic Solvents on the Catalytic Performance of Levansucrase from Zymomonas mobilis KIBGE-IB14 - Sidra Shaheen; Afsheen Aman; Nadir Naveed Siddiqui (Journal of Basic & Applied Sciences, 2017)
A significant progress has been made in discovering and developing new bacterial polysaccharides producing enzymes possessing extremely functional properties. Levan is a natural polymer of fructose linked by β (2→6) glycosidic bond which is produced by transfructosylation reaction in the presence of levansucrase. Among wide range of microorganisms, Zymomonas mobilis is considered as the most promising candidate for the production of extracellular levansucrase. It has potential applications in multiple industries from pharmaceutics, cosmetics to food industries. Determination of levansucrase characteristics is necessary to increase its industrial applications. This concept has directed much interest towards enzyme characterization by observing its effects against different chemicals. The present investigation focused on the characterization of levansucrase by observing its behavior with reference to different metal ions, surfactants and organic solvents. The results showed that these chemicals acted as activators, inhibitors or stabilizers. In metal ions, different activators (K+, Na+, Cs+, Ba+2, Ca+2, Cu+2, Mg+2 and Mn+2 ) and inhibitors (Co+2, Hg+2 , Fe+3and Al+3) were investigated. Among them, Hg+2 found to be strong inhibitor as it inhibits enzyme activity by 92% at 1 mM. Non-ionic surfactants i.e. triton X-100, tween-20 and tween-80 considered as stabilizers while anionic surfactant such as sodium dodecyl sulphate (SDS) inhibited the enzyme activity by 11%. Moreover, ethanol and methanol stabilized the enzyme activity while other solvents observed as inhibitors or stimulators.